Efficient separation of terephthalate and phthalate anions by selective ion-exchange intercalation in the layered double hydroxide Ca2Al(OH)(6)center dot NO3 center dot 2H(2)O - Millange, F; Walton, R; Lei, L; O'Hare, D (2000)
The brucite-like Ca2+/Al3+ layered double hydroxide (LDH), Ca2Al(OH)6·NO3·2H2O, was synthesized using the coprecipitation method. The dicarboxylate anion 1,4-benzenedicarboxylate can be selectively intercalated into the layered double hydroxide Ca2Al(OH)6·NO3·2H2O from an aqueous solution containing an equimolar mixture of the 1,2- and 1,4-benzenedicarboxylates. Time-resolved in situ energy-dispersive X-ray diffraction studies of the competitive intercalation reaction reveal that initially both the 1,2- and the 1,4-benzenedicarboxylates are intercalated in the LDH, followed by replacement of the 1,2-benzenedicarboxylate by the 1,4-isomer as the reaction proceeds. The final thermodynamic product is Ca2Al(OH)6·[1,4-C8H4O4]0.5H2O.